DIKSI MAJAS OKSIMORON DAN TERJEMAHANNYA DALAM ANTOLOGI PUISI “TIDAK ADA NEW YORK HARI INI” - I Gusti Agung Sri Rwa Jayantini; Ronald Umbas (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2018)
Karya sastra dan penerjemahan mempunyai peran penting dalam perkembangan bahasa. Cara berekspresi dengan menggunakan diksi dalam karya sastra, khususnya puisi dan terjemahannya memberi peluang bagi pengayaan kosa kata dan pendalaman makna. Penelitian ini merupakan kajian penerjemahan puisi yang berfokus pada diksi majas oksimoron. Analisis ditujukan untuk mengetahui jenis antonim dan strategi penerjemahan diksi bertentangan pada antologi puisi “Tidak ada New York Hari Ini” dan terjemahannya dalam bahasa Inggris. Metode kualitatif diterapkan dengan melakukan pengamatan (observation) dan analisis isi (content analysis) untuk mencermati diksi yang menciptakan nuansa bertentangan. Ada dua hal utama yang menjadi hasil penelitian ini. Pertama, diksi majas oksimoron dapat berupa (a) oposisi kembar yakni pertentangan mutlak dari dua leksikon, (b) gradual yakni leksikon bertentangan yang menunjukkan gradasi terukur, dan (c) relasional yakni oposisi yang memiliki kaitan hirarkis. Kedua, strategi penerjemahan secara harfiah dan harfiah-makna. Secara harfiah, penerjemahan dilakukan dengan padanan yang makna leksikalnya sesuai, sedangkan secara harfiah-makna penerjemahan dilakukan dengan menggunakan padanan alternatif untuk memberi kesan lebih estetis dan puitis. Kata Kunci: diksi, oksimoron, strategi penerjemahan, penerjemahan puisi DICTIONS OF OXYMORONIC EXPRESSION AND THEIR TRANSLATION IN THE POEM ANTHOLOGY “TIDAK ADA NEW YORK HARI INI”AbstractLiterary works and translation play a significant role in language development. The expression realized through dictions in literary works, particularly as found in a poem can encourage the enrichment of vocabulary and the exploration of meaning. This is a poetry translation study that is focused on dictions of oxymoronic expressions. It aims at investigating the types of antonym and strategies used to translate the dictions selected to represent the opposite atmosphere in the poem anthology “Tidak ada New York Hari Ini” and its translation in English. This study utilized qualitative method that was applied through close observation and content analysis on the dictions, which were chosen to create a contradictory situation. Two significant results were found in this study. First, this study showed that the dictions of oxymoronic expressions were classified into binary, gradable and relational antonyms. Binary opposition constitutes the oppositeness that cannot be measured. Gradable antonym is the word pairs whose meaning is possibly graded. Relational antonym is shown in the pairs of words that are related to each other through converse relations. Second, two translation strategies – literal translation and literal-meaning translation – were applied in translating the antonyms representing oxymoronic expressions. Literal translation was shown by the choice of utilizing established equivalent in the translation whose meaning is very close to the source language. Meanwhile, literal-meaning was applied to establish idiomatic translation through the utilization of alternative equivalents that were meant to give more aesthetic and poetic impressions. Keywords: diction, oxymoron, strategies of translation, poetry translation